Dreamscapes myth & magic creating legendary creatures & characters in watercolor - Law, Stephanie Pui-Mun (Ohio IMPACT Books, 2010)
Explores the ancient origins and demonstrates the author's techniques for creating fantasy characters, creatures and settings. This title enables the readers to learn to create the fantasy scenes step by step, including basic materials and techniques. It also helps you learn about planning and sketching.
Keywords: Animals, mythical in art; Watercolor painting -- Technique; Art -- Technique